THE DEMOCRATIC CRISIS AND DIGITAL RIGHTS: THE REPUBLICAN PRINCIPLE AS GUARDIAN OF COLLECTIVE RIGHTS AND CITIZENSHIP IN THE DEMOCRATIC STATE OF LAW (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
ABSTRACTThe contemporary democratic crisis, intensified by technological transformations and the rise of digital platforms, profoundly challenges the pillars of the Democratic Rule of Law and the active participation of citizens. The control of information, the dissemination of disinformation and the concentration of power in the hands of large technology corporations compromise the integrity of democratic institutions and the balance of public debate. In this scenario, digital rights – such as privacy, freedom of expression and access to information – become fundamental instruments in the defense of collective rights and the preservation of democracy.The republican principle, with its emphasis on justice, transparency and the common good, emerges as a guardian of these rights, offering a normative solution to face the threats posed by the digital environment and strengthen democratic governance. This article analyzes how the application of the republican principle in the regulation of digital platforms can ensure the protection of fundamental rights and guarantee equitable participation in the digital space. Furthermore, it discusses the importance of public policies that promote the protection of these rights and the integrity of democratic institutions, especially in times of crisis. By integrating the republican principle into digital governance, it is possible not only to preserve collective rights, but also to consolidate a rule of law that meets the demands of the digital age and the needs of citizens. Keywords: Democratic crisis. Digital rights. Republican principle. Collective rights. Citizenship. Democratic rule of law.